Validation of an airline pilot assistant system for low-noise approach procedures. (October 2021) - Jäger, David; Zellmann, Christoph; Wunderli, Jean Marc; Scholz, Marco; Abdelmoula, Fethi; Gerber, Martin
Graphical abstract: Highlights: Considerable noise reduction potential of pilot assistance system demonstrated. Average sound exposure levels reduced by up to 1.8 dBA during final approach. Average sound exposure levels reduced by up to 2.5 dBA in far range. Elimination of particularly loud approaches. Abstract: The recently developed airline pilot assistance system LNAS (Low Noise Augmentation System) supports pilots in optimizing approaches in terms of fuel consumption and noise emission by predicting the optimal vertical trajectory and best speed, configuration, and landing gear setting. The system continuously updates recommendations to provide the energy-optimal profile at any time. The noise reduction potential of the latest LNAS version was tested during a flight campaign in 2019 at Zurich Airport, Switzerland, using a dedicated Airbus A320 research aircraft. 43 LNAS-assisted and 21 conventional approaches were analyzed. Acoustic measurements taken at six microphone positions along the glide path revealed reductions in average sound exposure levels of up to 1.8 dBA when LNAS was used. Complementing detailed single-flight simulations using the aircraft noise program sonAIR confirmed the large noise reduction potential of LNAS, which may help reducing sound exposure in certain areas by up to 2.5 dBA.